ANALISIS KINERJA KEUANGAN KOPERASI SERBA USAHA ROKAN JAYA DESA RANTAU BINUANG SAKTI ROKAN HULU - -, S U D I R M A N (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2015)
Analysis Management financial statement represent all important matter in an effort with existence of ratio analysis aim to know monetary performance at Coperation Completely the Effort Glorious Rokan of Countryside Go Abroad Miraculous Binuang District Of Fullness of Rokan Pate Upstream by using ratio analysis of liukuiditas, solvability, rentability, and activity period of year 2011-2013 taken data in the form of report of keungan covering Balance and Lossy Report/ Profit pursuant to is fourth of used by variable is storey;level growth of Coperation effort as a whole experience of progress of analysis of likuiditas first in the year and second year obtaining percentage of7Coperation stadar though in recent year experience of degradation however managed is effort operation which is running and lay in percentage value 150 - 250 % with criterion still stabilize the effort which is experiencing. Storey Level analysis solvability lay in percentage value < 40 - 50% and percentage value < 70 - 100% in this case usah management party/ side where debt which in accounting by take careing same assess asset/ capital alone is so that still can be told to stabilize. rentability analysis at measurement of NPM, ROA, ATO, Rentability Capital alone from first year and natural the last year of speed growth of effort which in management by usah management party/ side and really pride upon from result of Coperation management performance so that memperolah above Coperation standard. natural Activity analysis fluctuate him assess percentage of effort Coperation of will effort management party side do conduct correction of converted farm however the value do not too having an effect on with effort which is run with a purpose to Coperation wish to stabilize him of is effort them of dimasa-masa come. Coperation Completely the Effort Glorious Rokan better each every effort which in management do not escape of from financial analysis thereby the effort which is run will always stabilize goodness